أثر استخدام منصة اليوتيوب في التعلم الذاتي لدى طلبة البكالوريا دراسة ميدانية بثانوية بشوشة المختلطة بالوادي - نجوى خطراوي; بشرى بكاكرة; براءة حميداتو (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى تقصي أثر توظيف منصة يوتيوب في دعم أنشطة التعلم الذاتي لدى فئة تلاميذ البكالوريا لثانوية بشوشة المختلطة بالوادي، في ظل تزايد الاعتماد على الوسائط الرقمية في العملية التعليمية. تمثل يوتيوب إحدى الأدوات الرقمية الشائعة، والتي باتت تستقطب اهتمام المتعلمين كمصدر بديل أو مكمل للمقررات التقليدية. اعتمد البحث منهجًا وصفيًا ذا طابع ميداني، مستندًا إلى إطار نظري يعرض مفاهيم مرتبطة بالتعلم الذاتي، خصائصه، أنماطه، ومتطلباته، إلى جانب خصائص المنصة الرقمية المدروسة. أما الجانب التطبيقي فتم من خلال استبيان وزّع على عينة من تلاميذ البكالوريا لثانوية بشوشة المختلطة، لاستكشاف مدى اعتمادهم على المنصة في مراجعة الدروس، وطبيعة الاستخدام، ومظاهر التفاعل مع المحتوى. أظهرت النتائج أن نسبة معتبرة من أفراد العينة (75%) يلجؤون إلى دروس الدعم، ويستخدم جزء كبير منهم يوتيوب كمصدر تعليمي مساعد. كما بيّنت المعطيات أن المحتوى الرقمي لا يُستثمر دائمًا بشكل فعّال، إذ أشار عدد من المبحوثين إلى صعوبات تتعلق بطول المقاطع، ضعف التنظيم، وتشوش المحتوى نتيجة غياب الانتقاء والجودة العلمية. تشير الدراسة إلى إدراك التلاميذ لتكامل يوتيوب مع المصادر التعليمية التقليدية، لا سيما الكتب المدرسية، مع بروز الحاجة إلى تأطير تربوي يوجه استخدام المنصة بشكل رشيد. توصي الدراسة بتعزيز التكوين الإعلامي والرقمي للتلاميذ، وتضمين استراتيجيات التعلم الذاتي المعتمد على الوسائط الجديدة في البرامج التعليمية. "This study aims to investigate the impact of using YouTube in supporting self-directed learning among Baccalaureate students at Bachoucha Mixed Secondary School in El Oued, in light of the growing reliance on digital media in the educational process. YouTube is one of the most widely used digital tools, attracting learners as an alternative or complementary source to traditional curricula. The research adopts a descriptive methodology with a fieldwork component. The theoretical framework addresses key concepts related to self-directed learning, its characteristics, types, and requirements, in addition to the educational features of YouTube. The practical part is based on a questionnaire distributed to a sample of Baccalaureate students at Bachoucha Mixed Secondary School in El Oued, aiming to explore their use of the platform for lesson review, usage patterns, and interaction with content. Findings reveal that a significant portion of the sample (75%) of Baccalaureate students at Bachoucha Mixed Secondary School in El Oued relies on external tutoring, with many using YouTube as a supplementary educational resource. However, the data also indicate that this content is not always utilized effectively. Students reported several challenges, such as long and poorly organized videos, as well as an overload of unverified content. The study highlights the perception of Baccalaureate students at Bachoucha Mixed Secondary School in El Oued regarding the complementarity between YouTube and traditional educational resources, particularly textbooks. It stresses the need for educational guidance to promote purposeful use of the platform. The study recommends strengthening students’ digital and media literacy and incorporating self-learning strategies based on new media into educational programs.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: تلاميذ البكالوريا; تعلم ذاتي; اليوتيوب; YouTube; self-directed learning; Baccalaureate level